2016
DOI: 10.2147/copd.s113625
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the T-cell profiles of the airways in COPD patients associated with clinical phenotypes

Abstract: T lymphocytes are believed to play an important role in the pathogenesis of chronic obstructive pulmonary disease (COPD). How T cells are recruited to the lungs and contribute to the inflammatory process is largely unknown. COPD is a heterogeneous disease, and discriminating disease phenotypes based on distinct molecular and cellular pathways may provide new approaches for individualized diagnosis and therapies. Bronchoalveolar lavage (BAL) and blood samples were obtained from 40 never-smokers, 40 smokers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…While the end goal of the unsupervised workflow presented here is to perform molecular sub-classification of all or at least several of the existing COPD sub-phenotypes, any study evaluating the performance of this method absolutely must focus on a COPD subgroup that can be expected to have molecular similarities to ours. The existence of a female-dominated molecular COPD phenotype in the Karolinska COSMIC cohort has been well established in our findings from supervised analyses of the single-omics data blocks [17,21,23,30]. The female part of the Karolinska COSMIC cohort thus provides a set of molecularly distinct ground-truth study groups to evaluate the unsupervised classification.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While the end goal of the unsupervised workflow presented here is to perform molecular sub-classification of all or at least several of the existing COPD sub-phenotypes, any study evaluating the performance of this method absolutely must focus on a COPD subgroup that can be expected to have molecular similarities to ours. The existence of a female-dominated molecular COPD phenotype in the Karolinska COSMIC cohort has been well established in our findings from supervised analyses of the single-omics data blocks [17,21,23,30]. The female part of the Karolinska COSMIC cohort thus provides a set of molecularly distinct ground-truth study groups to evaluate the unsupervised classification.…”
Section: Discussionmentioning
confidence: 54%
“…This study used omics data blocks from the Karolinska COSMIC cohort (ClinicalTrials.gov ID: NCT02627872), a three-group cross-sectional study [17][18][19][20][21][22][23][24][25] with age-matched (45-65 years) and sex-matched groups of healthy never-smokers ("Healthy"), smokers with normal lung function ("Smokers") and COPD patients ("COPD"; Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage I-II/A-B; FEV1 51-97%; FEV1/FVC <70) (table E1). Peripheral blood, bronchoalveolar lavage (BAL) and bronchial epithelial cells (BEC) were collected as previously described [17,19].…”
Section: Clinical Cohortmentioning
confidence: 99%
“…Consistent with previous reports (37)(38)(39)(40), the present study demonstrated high expression of the chemokine receptors CCR5 and CXCR3 (markers of Th1 cells) and CCR6 (Th17 marker) in nearly 100% of CD4+ T cells isolated from the BAL fluid of both anti-Jo-1+ and anti-Jo-1− patients. The enriched expression of these chemokine receptors in BAL fluid T cells compared to peripheral blood T cells was not unexpected, as several studies have shown that these receptors are known to regulate antigeninduced T cell homing in lung diseases, such as asthma (41,42), COPD (43), and sarcoidosis (44), and can even be found in healthy smokers (45). Moreover, the identification of a Th1/Th17 phenotype (Th17.1 cells) in BAL fluid from patients with IIM/antisynthetase syndrome, characterized by an excessive secretion of IFNγ, has also been reported in patients with chronic sarcoidosis (38,46,47) and in other autoimmune diseases such as Crohn's disease (48) and arthritis (49).…”
Section: Discussionmentioning
confidence: 92%
“…T lymphocytes are an important component of the adaptive immune system and their levels are higher in patients with COPD. 44 T lymphocytes are directed to the site of inflammation when chemokines expressed on their surface bind to chemokine receptors. 44 An analysis of chemokines and T-cell chemokine receptor expression in never-smokers, smokers with normal lung function, and patients with COPD showed a higher expression of the chemokine receptor CCR5 on CD8+ T cells in the blood of women smokers compared with men smokers, indicating a genderdependent T-cell profile in COPD.…”
Section: Dysregulated Immune Cell Function and Autophagymentioning
confidence: 99%
“…44 T lymphocytes are directed to the site of inflammation when chemokines expressed on their surface bind to chemokine receptors. 44 An analysis of chemokines and T-cell chemokine receptor expression in never-smokers, smokers with normal lung function, and patients with COPD showed a higher expression of the chemokine receptor CCR5 on CD8+ T cells in the blood of women smokers compared with men smokers, indicating a genderdependent T-cell profile in COPD. 44 This difference in the expression of chemokine receptors could contribute, for instance, to gender differences in disease susceptibility.…”
Section: Dysregulated Immune Cell Function and Autophagymentioning
confidence: 99%